124 Validation of the BCIS-1 myocardial Jeopardy score using cardiac MRI. (9th June 2011) - Morton, G D J; De Silva, K; Ishida, M; Chiribiri, A; Indermuhle, A; Schuster, A; Redwood, S; Nagel, E; Perera, D
Abstract : Introduction: The recently described angiographic BCIS-1 Myocardial Jeopardy Score (BCIS JS) was designed to classify the extent of coronary artery disease (CAD). It provides a semi quantitative estimate of the amount of myocardium at risk as a result of severe coronary stenoses (0=no jeopardy; 12=maximum jeopardy). Advantages include ease of use and universal applicability including classification of left main stem disease and CABG. However anatomic tests, including the BCIS JS, do not incorporate myocardial ischaemia and scar, which are important for management and prognosis. Cardiac magnetic resonance (CMR) imaging allows reliable assessments of myocardial ischaemia and scar in a single examination and was used to examine the functional relevance of the BCIS JS. Methods: 60 consecutive patients with angina and known or suspected CAD referred for diagnostic x-ray coronary angiography underwent CMR examination at a single UK centre. CMR included standard functional and scar imaging and also high-resolution k-t accelerated adenosine stress and rest perfusion imaging at 1.5T (40 patients) or 3T (20 patients). Expert observers blinded to the clinical data analysed the angiographic and CMR data. The BCIS JS was calculated from visual analysis of the coronary angiogram. CMR perfusion and scar data were segmented according to the standard 17-segment model excluding the apex. Segments were subdivided into equal endo- and epicardial sub-segments, each assigned 3% of the total myocardial volume and classified as normal, ischaemia or scar. Myocardial ischaemia and scar burden were calculated and correlated with the BCIS JS individually and as a combined score (Abstract 124 figure 1 ). Results: Patient characteristics are summarised in the Abstract 124 table 1. 2 patients were excluded (1 claustrophobia; 1 incomplete imaging data). Mean interval ± SD between CMR and coronary angiography was 40±47 days. 13 patients (22%) with no history of myocardial infarction had CMR evidence of prior infarction. There was a strong correlation between the BCIS JS and myocardial ischaemic burden: Pearson's r=0.75, p<0.00001 (Abstract 124 figure 2 ). The BCIS JS was also correlated with the combined burden of scar and ischaemia: r = 0.77, p<0.00001. There was no difference between 3T and 1.5T CMR imaging. Area under the receiver-operating characteristic curve for BCIS JS to detect ≥10% myocardial ischaemic burden was 0.87 (95% CI 0.77 to 0.97). BCIS JS ≥6 predicted ≥10% myocardial ischaemic burden with sensitivity 68% and specificity 90%. Conclusions: The BCIS JS correlated well with ischaemic burden on CMR. A BCIS JS ≥6 predicts the prognostically important ischaemic threshold of 10% with high specificity. As expected, the correlation is imperfect which is likely to be a result of difficulty predicting haemodynamic effects of angiographically moderate disease, microvascular disease and limitations of CMR imaging.